Accelerated growth and local progression of radiorecurrent prostate cancer in an orthotopic bioluminescent mouse model - Gavin Frame; Xiaoyong Huang; Roni Haas; Kabir A. Khan; Hon S. Leong; Thomas Kislinger; Paul C. Boutros; Michelle Downes; Stanley K. Liu (Scientific Reports)
Abstract Globally, prostate cancer is the second most common malignancy in males, with over 400 thousand men dying from the disease each year. A common treatment modality for localized prostate cancer is radiotherapy. However, up to half of high-risk patients can relapse with radiorecurrent prostate cancer, the aggressive clinical progression of which remains severely understudied. To address this, we have established an orthotopic mouse model for study that recapitulates the aggressive clinical progression of radiorecurrent prostate cancer. Radiorecurrent DU145 cells which survived conventional fraction (CF) irradiation were orthotopically injected into the prostates of athymic nude mice and monitored with bioluminescent imaging. CF tumours exhibited higher take rates and grew more rapidly than treatment-naïve parental tumours (PAR). Pathohistological analysis revealed extensive seminal vesicle invasion and necrosis in CF tumours, recapitulating the aggressive progression towards locally advanced disease exhibited by radiorecurrent tumours clinically. RNA sequencing of CF and PAR tumours identified ROBO1, CAV1, and CDH1 as candidate targets of radiorecurrent progression associated with biochemical relapse clinically. Together, this study presents a clinically relevant orthotopic model of radiorecurrent prostate cancer progression that will enable discovery of targets for therapeutic intervention to improve outcomes in prostate cancer patients.